Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh - Paulsen, M.j. (Zootaxa, 2017)
The endemic North American stag beetle tribe Platyceroidini Paulsen & Hawks (Coleoptera: Lucanidae: Lucaninae) is reviewed. All primary types were studied and the existing generic and species concepts are subsequently corrected. Based on study of the male genitalia and external morphology, the previously monotypic genus Platyceropsis Benesh is reduced to subgeneric status under Platyceroides Benesh, new status, and the species Platyceroides laticollis (Casey) and Platyceroides keeni (Casey) new combination are transferred to this subgenus. Praocerus, new subgenus, is created to contain the species Platyceroides latus (Fall), and P. viriditinctus (Benesh). In the nominal subgenus, confusion has resulted from the historic misapplication of the oldest available name, Platyceroides agassii (LeConte), resulting in significant underestimation of the number of extant taxa. Lectotypes are designated for four species-group names (listed in their original combinations): Platycerus latus Fall, Platycerus opacus Fall, Platycerus pacificus Casey, and Platycerus parvicollis Casey. Four new species (Platyceroides barrae, P. infernus, P. pampinatus, and P. umpquus) are described from California and Oregon, United States of America. The following species are valid and are removed from synonymy with P. agassii: P. pacificus (Casey), revised status, and P. californicus (Casey), revised status. The synonym Platycerus parvicollis Casey is transferred from Platyceroides agassii to P. californicus, new synonymy. With the addition of four new species and the correction of the mistaken synonymies the total number of species in the tribe Platyceroidini is now 16.